2018
DOI: 10.3390/cancers10110440
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation by lncRNAs: An Overview Focused on UCA1 in Colorectal Cancer

Abstract: Colorectal cancers have become the second leading cause of cancer-related deaths. In particular, acquired chemoresistance and metastatic lesions occurring in colorectal cancer are a major challenge for chemotherapy treatment. Accumulating evidence shows that long non-coding (lncRNAs) are involved in the initiation, progression, and metastasis of cancer. We here discuss the epigenetic mechanisms through which lncRNAs regulate gene expression in cancer cells. In the second part of this review, we focus on the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 339 publications
(190 reference statements)
0
35
0
Order By: Relevance
“…LncRNAs are often dysregulated in the pathological processes of CRC, functioning as oncogenes or tumour-suppressors [3,34,35,39]. For example, lncRNA DLEU1 promotes CRC cell proliferation and migration by recruiting SMARCA1, a subunit of the NURF chromatin remodelling complex, to the promoter of KPNA3, a gene whose expression is associated with a lower survival rate and poorer prognosis in CRC patients [40].…”
Section: The Interplay Between Non-coding Rnas and Epigenetics In Crcmentioning
confidence: 99%
“…LncRNAs are often dysregulated in the pathological processes of CRC, functioning as oncogenes or tumour-suppressors [3,34,35,39]. For example, lncRNA DLEU1 promotes CRC cell proliferation and migration by recruiting SMARCA1, a subunit of the NURF chromatin remodelling complex, to the promoter of KPNA3, a gene whose expression is associated with a lower survival rate and poorer prognosis in CRC patients [40].…”
Section: The Interplay Between Non-coding Rnas and Epigenetics In Crcmentioning
confidence: 99%
“…23 Recent evidence has highlighted the crucial regulatory roles of ceRNA networks in colorectal cancer. 24,25 Many studies have shown that multiple lncRNAs, such as CACS15, 26 KCNQ1OT1, 27 and BLACAT1, 28 and multiple miRNAs, such as miR-625-3p, 29 miR-34a, 30 miR-483-3p, 31 and miR-122, 32 are associated with oxaliplatin resistance. In this study, the ceRNA network was constructed based on RNA information obtained from bioinformatics analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Further results showed positive relationships in lncRNA expressions between tissues and plasmas in patients with hepatocellular carcinoma (Wang et al, 2018) and colorectal cancer (Neve et al, 2018). Compared to the tissues, isolation of nucleic acids from plasma serves as an ideal method for early and differentiation diagnosis, evaluation the medication responses, and assessment of the prognosis.…”
Section: Discussionmentioning
confidence: 97%